This Time It's Different: The Role of Women's Employment in a Pandemic Recession - Titan Alon; Matthias Doepke; Jane Olmstead-Rumsey; Michèle Tertilt (Institute of Labor Economics (IZA), 2020)
In recent US recessions, employment losses have been much larger for men than for women. Yet, in the current recession caused by the Covid-19 pandemic, the opposite is true: unemployment is higher among women. In this paper, we analyze the causes and consequences of this phenomenon. We argue that women have experienced sharp employment losses both because their employment is concentrated in heavily affected sectors such as restaurants, and due to increased childcare needs caused by school and daycare closures, preventing many women from working. We analyze the repercussions of this trend using a quantitative macroeconomic model featuring heterogeneity in gender, marital status, childcare needs, and human capital. Our quantitative analysis suggests that a pandemic recession will i) feature a strong transmission from employment to aggregate demand due to diminished within-household insurance; ii) result in a widening of the gender wage gap throughout the recovery; and iii) contribute to a weakening of the gender norms that currently produce a lopsided distribution of the division of labor in home work and childcare.
Keywords: D13; E32; J16; J20; 330; COVID-19; pandemics; recessions; business cycle; gender equality; school closures; childcare; gender wage gap